Effective design and assessment of an MBA degree program through benchmarking - Khalid M. Dubas (Innovative Marketing, 2017)
This study describes how Mount Olive College, a four-year liberal arts college in Eastern North Carolina, designed and successfully implemented an MBA degree program. This led to the establishment of a graduate school, change of status from college to university, and development and offering of additional graduate degree programs. The University of Mount Olive (UMO) started offering this MBA degree program in spring 2014. This online degree program has been offered in an accelerated one-year format and in a traditional two-year format. This program has been very successful and enrollment continued to grow. As of fall 2017, the UMO MBA program was the 9th largest MBA degree program in North Carolina. A two-year assurance of learning and outcomes assessment was recently completed and the results showed that the UMO MBA faculty successfully aligned the course Student Learning Outcomes (SLOs) with the MBA program goals and Program Learning Outcomes (PLOs). This assessment provided valuable insights that are presented in this study. UMO has planned to soon offer a hybrid (face-to-face seated plus online) MBA degree program and a healthcare MBA degree program.